Xamarin.Forms Solutions - Versluis, Gerald, ....-; Thewissen, Steven, ....- (Hulsberg : Apress, 2019)
Use the solutions provided in this book to handle common challenges in Xamarin.Forms that are encountered on a daily basis. Working examples and techniques are presented that you can modify and drop directly into your own projects. You will be able to deliver working code faster than ever. Examples are made available through GitHub, maximizing the convenience and value this book provides to Xamarin.Forms developers. Solutions in the book are organized broadly into problem domains such as user interface for applications, data and security, connectivity and external services, and more. Within each domain the book presents specific solutions addressing challenges that are commonly faced. Under data and security, for example, you'll find specific solutions around storing login credentials, local data caching, and sending authorization tokens in HTTP requests. Not only do the solutions in the book solve specific problems, they also present best practices that can inform and improve the quality of the code that you write. Xamarin.Forms Solutions is chock full of practical advice and code examples that no Xamarin.Forms programmer will want to be without. The basics of Xamarin.Forms are provided for beginning developers. What You'll Learn •Know the in-depth basics of Xamarin.Forms and the inner workings •Create custom renderers and dependency services •Manage the appearance of user interfaces through styling and theming, layout options, rotation, and animation •Build sophisticated user interfaces using a variety of controls that allow for PDF viewing, barcode interpretation, searching and finding, and other controls •Secure your applications, and communicate securely with services via HTTP requests •Sign and deploy your apps and optimize the binary file size
Keywords: Xamarin.Forms.